Variability of Fatty Acids Composition of Wild Sumac (Rhus coriaria L.) Fruit - N Nayebpour; HA Asadi-Gharneh (Institue of Medicinal Plants, ACECR, 2019)
Background: Sumac (Rhus coriaria L.) belongs to Anacardiaceae family. The dried and powdered fruits are used as a food flavoring and medicinal plant. Objective: In this study, variability of fatty acid composition in some wild sumac fruits were investigated. Method: The samples were collected from their natural origins in central parts of Iran; Isfahan and Markazi province in the September to October, 2016. The morphological characters of fresh fruits were measured. Also oil content and profile of fatty acids composition were measured. Results: Results indicated that there are significant differences between morphological characteristics, oil percent and fatty acids compositions of wild sumac fruit populations. The range of oil percent of Iranian sumac population was 9.22% to 15.33%. The major oil quantity contained unsaturated fatty acids (64.75%- 74.08%) followed by saturated fatty acids (25.84%- 35.13%). Among saturated fatty acids, palmitic was evaluated as the highest value (21.36- 29.79 %) while the most unsaturated fatty acids were oleic acid (36.65- 44.74 %) and linoleic acid (22.62- 33.48 %). Also, soil and geographical characteristics show significant relationship with fatty acids quantity in this study. Conclusion: According to our results concluded that the differences between fatty acids of sumac fruits may be related to the growth conditions like soil and geographical characteristics. Also, this study demonstrates that sumac can be a good source of fatty acids and could be useful for human nutrition.